Minat Melanjutkan Pendidikan Ke Perguruan Tinggi Pada Siswa Kelas XII SMK Islam Assalafiyah Cibiuk – Garut (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
Education is one of the main means to develop the potential or abilities possessed by the younger generation of a country, so that they can become qualified individuals and benefit society. The purpose of the research is to find out what factors influence the interest of vocational students to continue their education to college. This research was conducted descriptively quantitatively and used frequency distribution to analyze responses from 47 students of class XII Computer & Network Engineering Department at SMK Islam Assalafiyah. The results of the analysis show that the majority of students have a higher interest in continuing their education to college, and internal factors, especially the drive to achieve a successful career, are the main causes of this interest.